KHARISMATIK PEMIMPIN DALAM BHISMA PARWA - I Nyoman Subagia; I Putu Agus Aryatnaya Giri (Guna Widya: Jurnal Pendidikan Hindu, 2020)
In the environment of life such as family, school, and society can not be avoided from the charismatic system of a leader, both as a leader and as a leader who is led. The fact that there are several things that cause the lack of charismatic leaders. Related to this, then in this study offers the charismatic leaders in Bhishma Parwa, this research is a literature study that is described in a qualitative descriptive manner, with the charismatic results of a leader in Bhishma Parwa emphasized on the element of innate human traits from birth, but on the side Another charismatic can be built on a person through learning, doing good deeds, as well as fostering a spiritual feel within.